Serum Prolactin Concentration in Patients with Pemphigus Vulgaris (Mugda Medical College Journal, 2023)
Background: Pemphigus vulgaris (PV) is an autoimmune bullous disorder characterized clinically by blisters and erosions of the skin and/or mucous membranes. Serum prolactin plays a role in the pathogenesis of pemphigus vulgaris.Objective: The study aims to observe the serum prolactin concentration in patients with pemphigus vulgaris.Methods: This cross-sectional study was conducted at the Department of Dermatology & Venereology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, between May 2017 and April 2018. A total of 35 patients were included in the study. A consecutive type of sampling technique was used. The dermatological examination was done to ascertain the extent of involvement of the disease.Results: Among 35 patients, 31.4% belonged to 30-50 years age group, while 62.9% belonged to >50 years and 5.7% patients belonged to